KAJIAN PENGEMBANGAN SISTEM TENAGA LISTRIK KOTA KENDARI PROVINSI SULAWESI TENGGARA - Agustinus Lolok; La Ode Muh. Magribi; Mustarum Musarudin (Universitas Halu Oleo, 2018)
This study aimed to (1) analyze the future needs for electricity in Kendari city in the sectors ofhousehold, commerce, public, and industry; (2) analyze the capaity of power plant than can serve the whole cityof Kendari today: and (3) analyze the plan for developing electricity in Kendari city based on Rencana TataRuang Wiayah Kota Kendari (RTRW) 2010-2030. The study was conducted by analyzing electrical needs invarious sector of electricity consumers in Kendari city, the capacity of electricity power plant that servedKendari city in 2015, and the plan for developing electricity in Kendari city as well as the spatial plan forKendari city in the RTRW of Kendari city for 2010-2030. Based on the results of data processing and analysis,it could be concluded that (1) the needs for electricity in Kendari City will increase from year to year in 2016-2025. Ranked from the largest to the smallest, the needs for electricity in Kendari City were in the followingsectors: households, business, public, industry, and special services, and the total consumption of electricity inKendari City in 2025 is 575.96 GWh and the needs for power is 156.5 MW; (2) The existing power plant (85,4MW) will only be able to serve the city until 2017. In 2018, PLN have to build new power plants, complete theconstruction of PLTU, or revitalize non-functional power plants. New power plants with a capacity of 33.8 MWto the minimum will be needed within a period from 2022 to 2025; (3) The plan for constructing new powerplant in the subdistrict of Abeli and creating a new network in the subdistricts of Abeli, Poasia, Baruga, Kambu,Wua-Wua, Kadia, and Puuwatu as stated in RTRW of Kendari City for 2010-2030 is considered correct, sincethe needs for electricity in those areas will continue to grow with the developement in industry, warehouse,redinteal areas with high density, residential areas with medium density, business areas, and office complex.KeywordS: electricity need, capacity of power plant